â€œSUDAH TIDAK TERSUDU OLEH ANGSA, BARU DIBERIKAN KEPADA ITIKâ€: PERSPEKTIF SEMANTIK INKUISITIF DAN AKAL BUDI MELAYU - Daud, Muhammad Zaid; Subet, Mary Fatimah (JURNAL MELAYU SEDUNIA, 2019)
Malay proverb â€œSudah tidak tersudu oleh angsa, baru diberikan kepada itikâ€ means â€œThings that are useless to rich people which are then given to the poorâ€ have been obtained from Kamus Peribahasa Istimewa Peribahasa Melayu by Abdullah Hussain (2016) based on purposive sampling. However, the study of the meaning of the proverb is inadequate to be fully understood why the Malay community in ancient times used the symbol of animals to refer to human deeds. The meaning of proverbs has shown that Malay society in the past was wide for successfully associating animal images like a swan or scientific name is Anserini and duck or scientific name is Anas platyrhynchos with human behavior implicitly. Therefore, in response to the question, the Inquisitive Semantics approach by Nor Hashimah Jalaluddin (2014) is able to be applied by taking into authentic data, semantic and contextual data, cognitive speaking, and culture as well as ultimately attributed to the speaker’s mind. The application of Bridging Cross Reference (BCR) is also used to provide additional antecedents to researchers as the corpus data referred to through the Pangkalan Korpus Dewan Bahasa dan Pustaka (DBP) and the Malay Concordance Project (MCP) is an example of the use and actual examples of usage of the language that has been adopted by everyday people. Hence, based on these references it is able to describe the true context of the proverb to the speaker’s mind.